Evaluating the efficiency of the Iraqi banking sector using the data envelope analysis method: (دراسة تحليلية لعينة من المصارف العراقية الخاصة المدرجة في سوق العراق للأوراق المالية للمدة من ( 2005 – 2016) - Ahmed Faris, Ali; Ahmad Mahdi Al-Yasarii, Hisham (Iraqi Journal for Administrative Sciences, 2024)
The study aimed to measure the banking efficiency of a sample of Iraqi private commercial banks for the period from 2005 - 2016 and to know the concepts of banking efficiency and its relationship to performance, effectiveness and productivity, as well as an analysis of banking efficiency, and to achieve the goals of this study, the data envelope analysis method has been applied to the data of (10) Iraqi commercial banks Especially for the period 2005 - 2016 using the variable size return method (VRS). The study used a set of financial indicators and statistical equations to reach its results, the results of the financial analysis indicated that there is a difference in the average banking efficiency of commercial banks for the study sample, and that the most important recommendations presented by the study, the need for commercial banks for the study sample to adopt scientific and objective methods and methods that are It would increase the efficiency of its banking operations.